2023
DOI: 10.3390/nu15040989
|View full text |Cite
|
Sign up to set email alerts
|

Açaí (Euterpe oleracea Mart.) in Health and Disease: A Critical Review

Abstract: The açaí palm (Euterpe oleracea Mart.), a species belonging to the Arecaceae family, has been cultivated for thousands of years in tropical Central and South America as a multipurpose dietary plant. The recent introduction of açaí fruit and its nutritional and healing qualities to regions outside its origin has rapidly expanded global demand for açaí berry. The health-promoting and disease-preventing properties of this plant are attributed to numerous bioactive phenolic compounds present in the leaf, pulp, fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 196 publications
0
23
0
1
Order By: Relevance
“…For the lunch and dinner, he also increased his meals for 20%–25% (due to higher calories needed), which was all covered by vegetables. In the period of vacation (in Brazil), he did have everyday portion of 300 mL acai, which is very well know super‐antioxidant 24 . Clinical trials have suggested that acai can protect against metabolic stress induced by oxidation, inflammation, vascular abnormalities, and physical exertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the lunch and dinner, he also increased his meals for 20%–25% (due to higher calories needed), which was all covered by vegetables. In the period of vacation (in Brazil), he did have everyday portion of 300 mL acai, which is very well know super‐antioxidant 24 . Clinical trials have suggested that acai can protect against metabolic stress induced by oxidation, inflammation, vascular abnormalities, and physical exertion.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its medicinal properties and the absence of undesirable effects, acai shows a promising future in health promotion and disease prevention, including also male infertility. 24 Obesity in combination with aging and potentially diabetes could be a problem in male low sperm count. However, in this case, patient was having healthy situation with fat percentage between 11 and 18, and muscular percentage of the body between 42 and 49 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Açai has become more popular and exported worldwide, as it does not only provide foods, but also possesses numerous bioactive properties in the leaf, pulp, fruit, bark, and seeds [8]. Roots can be used as herbal medicine and tonic [10].…”
Section: Prospects and Challenges Of Açai Domestication In Indonesiamentioning
confidence: 99%
“…(Arecaceae) is a native tropical peat swamp forest of Central and South America; it distributes in the Amazonian, Peruvian, Venezuela and Suriname. E. oleracea is known as açai in Portuguese [7][8] or 'podosiri' in Surinamese [9]. Açai grows naturally along the riverbank, 1315 (2024) 012063 IOP Publishing doi:10.1088/1755-1315/1315/1/012063 2 forest-dominant palm species grow on marginal land that is unsuitable for agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation